The Fostering and Developing Students' Entrepreneurial Intentions Through Entrepreneurship Curriculum and Self-Efficacy: Evidence From Regression Analysis - Prastiko, Mufti Nawang; Mustiningsih, Mustiningsih; Sumarsono, Raden Bambang (Universitas Islam Kadiri, 2024)
The objective of this study is to identify and determine the level and impact of the entrepreneurship curriculum and self-efficacy on students' entrepreneurial intentions. This research employs a quantitative approach, utilizing descriptive analysis and multiple linear regression with partial t-tests and simultaneous f-tests. The study involves a sample of 100 students from faculties of Mathematics and Science (FMIPA), Engineering (FT), Education (FIP), and Letters (FS) at Universitas Negeri Malang. The sample size was determined using quota sampling, which provides researchers the flexibility to decide the number of participants. First, the entrepreneurship curriculum, manifested through entrepreneurship education, was rated as